Silicon-oxygen-carbon negative electrode material and preparation method and application thereof
By constructing a three-dimensional cross-linked stable carbon layer with graphitized carbon tubes and amorphously coated carbon cross-through, the problems of poor conductivity and insufficient cyclic stability of silicon oxygen negative electrode materials are solved, and their specific capacitance and cyclic stability are significantly improved.
Patent Information
- Application Number
- CN202411681447.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
AI Technical Summary
The poor conductivity, low capacity and insufficient cycling stability of silicon oxygen negative electrode materials limit their application in lithium-ion batteries.
Through the attraction of protonated amino organic matter and silicon oxygen, combined with the electrostatic action of metal ions and the formation of carbon tubes, a three-dimensional cross-linked stable carbon layer with graphitized carbon tubes and amorphously coated carbon cross-through is constructed to enhance the conductivity and structural stability of the material.
The specific capacitance and cycling stability of the silicon oxygen carbon negative electrode material are significantly improved. The specific capacity for the first charging can reach 1741mAh/g, and the battery capacity retention rate reaches 80% in 300 weeks.
Smart Images

Figure CN119542387A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemistry and to the preparation of silicon monoxide negative electrode materials. Background Art
[0002] At present, the negative electrode materials of lithium-ion batteries are mainly graphite, accounting for up to 98%. The specific capacity of graphite negative electrodes is above 350mAh / g, which is close to the theoretical specific capacity upper limit of 372mAh / g. Silicon-based negative electrodes have obvious advantages, with a theoretical specific capacity of up to 4200mAh / g, which is more than 10 times that of graphite materials. In addition, silicon can provide channels for lithium ion insertion and extraction from all directions, and has excellent fast charging performance. It is the development direction of negative electrodes in the future. However, the serious volume expansion of silicon-based negative electrodes during the lithium insertion process, poor material conductivity, first efficiency and cycle performance have restricted its commercial application. At present, pre-lithium silicon-oxygen negative electrode materials have the inherent advantage of high first coulomb efficiency, but their cycle stability is poor, and the material preparation cost is significantly high. , etc., have not been able to enter the power battery supply chain. In order to promote the industrialization of silicon-oxygen negative electrode materials, from the perspective of material market cost and comprehensive electrical performance, it is the best choice to solve the problems of cycle stability and low specific capacity from the perspective of surface carbon coating stability and conductivity, and then promote its application.
[0003] In response to the above problems, researchers have conducted a lot of research. Chinese patent CN114284481A discloses a high-rate silicon-oxygen-carbon material and its preparation method and application, which includes a silicon oxide core from the inside to the outside, a conductive three-dimensional network 1, a porous carbon layer or at least one of a porous carbon layer containing a conductive agent 2, and a coated carbon layer 3. By coating the three-layer conductive layer to suppress the expansion of silicon and oxygen, and maintain the integrity of the carbon coating layer after expansion, the conductivity of the composite material is improved. This method designs a multi-layer conductive agent coating to improve the conductivity of the material. However, the multi-layer coating strategy will inevitably lead to increased process complexity and the introduction of non-Li active substances, resulting in a decrease in the specific capacity of the negative electrode material, offsetting the capacity increased by the improved conductivity. In addition, there is a lack of internal forces between the three-layer coated carbon layers and between the organic carbon and the conductive agent, which makes it difficult to achieve the best stability of the coating structure. Patent CN107994225A discloses a porous silicon-carbon composite negative electrode material and its preparation method, and a lithium-ion battery. In the invention, a metal organic framework compound and a modified carbon nanotube jointly form a coating on nano silicon. In the specific method, metal salts and organic ligands are dispersed and reacted in an organic solvent to generate a metal organic framework compound, and then the solvent is removed to obtain a metal framework organic compound / silicon / modified carbon nanotube composite material. The modified carbon tube and the organic ligand are chemically bonded, and the nano silicon is further embedded in the holes of the MOF skeleton structure, and a carbon-coated nano silicon structure is formed after carbonization. However, this method is only suitable for nano silicon materials with a particle size of 20-200nm, and the preparation of metal MOF by this method requires an organic solvent, which brings risks and increases industrial costs.
[0004] Both of the above schemes are based on improving the electrical properties of negative electrode materials by improving the conductivity of materials and the density of coating structures, and the coating structure design tends to be physical composite, which has no positive effect on the capacity and cycle retention of the coated carbon layer during the charge and discharge process. There are obvious deficiencies in improving the conductivity of negative electrode materials and process economy. The prepared silicon-based negative electrode materials are difficult to improve the high-rate (1A / g) cycle stability and specific capacity. Therefore, it is very necessary to develop a preparation method to improve the surface coating uniformity and conductivity of silicon-oxygen negative electrode materials. Summary of the invention
[0005] In order to solve the technical problems of poor conductivity, low capacity utilization and high-rate cycle stability of silicon-oxygen negative electrode materials, the present invention proposes a silicon-oxygen-carbon negative electrode material and its preparation method and application. Based on the attraction between protonated amino organic matter and silicon-oxygen Si-O-terminal bonds, the amino groups on the surface of silicon-oxygen further form bonds with graphitized carbon such as carbon tubes under the electrostatic action of metal ions to form a three-dimensional cross-linked stable carbon layer with graphitized carbon tubes and amorphous coated carbon. This coated carbon has three advantages: first, the abundant nitrogen atoms in the carbon layer can effectively play a doping role, forming electronic defects to improve the conductivity of the carbon layer; second, the protonated amino groups and silicon-oxygen attract each other to form a uniform coating; third, the carboxyl graphitized carbon bonds on the basis of the amino-anchored silicon-oxygen surface, enhancing the compactness and stability of the carbon layer structure, effectively exerting its conductivity and structural stability, and promoting the reversible charge and discharge capacity.
[0006] To achieve the above object, the technical solution of the present invention is implemented as follows: A method for preparing a silicon oxygen carbon negative electrode material, the steps are as follows: (1) Dispersing conductive carbon in deionized water to obtain a dispersion; grinding the dispersion, adding a stabilizer to disperse the dispersion, and then adding silicon oxide powder to obtain a suspension; (2) dispersing an amino organic compound in deionized water, adding glacial acetic acid to form a protonated solution A; adding a metal salt to solution A to form a solution B; adding the suspension to solution B under stirring conditions, subjecting the solution to a chemical reaction, and spray drying to obtain a precursor; (3) In an inert atmosphere, the precursor is carbonized at high temperature to obtain the silicon-oxygen-carbon negative electrode material.
[0007] In the above step (1), the conductive carbon is one or more of carboxylated single-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes and carboxylated graphene; and the stabilizer is one or more of carboxymethyl cellulose, polyvinyl pyrrolidone and N,N-dimethylformamide.
[0008] In the above step (1), the amount of stabilizer added is 0.4-1wt% of the mass of the dispersion; the mass ratio of silicon dioxide powder to conductive carbon is 1000-2000:1.
[0009] In the above step (2), the amino organic compound is at least one of chitosan, polyethyleneimine derivatives, chitosan derivatives, polyethyleneimine and dopamine; the metal salt is Pd 2+ 、Co 2+ 、Ni 2+ 、Zn 2+ Cu 2+ nitrate or acetate.
[0010] In the above step (2), the mass of the amino organic compound is 10-30% of the mass of silicon oxide.
[0011] In the above step (2), the mass ratio of the amino organic compound, glacial acetic acid and metal salt in solution B is 1:1.5:(0.3-1).
[0012] The temperature of the chemical reaction in the above step (2) is 50-90°C.
[0013] In the above step (3), the high temperature carbonization temperature is 700-800°C and the time is 1-5h.
[0014] Furthermore, in the above step (3), the inert atmosphere is pure inert gas such as argon and nitrogen.
[0015] The silicon-oxygen-carbon negative electrode material prepared by the above-mentioned preparation method is composed of a three-dimensional cross-linked stable carbon layer coated on the surface of silicon oxide. The three-dimensional cross-linked carbon layer is formed by high-temperature carbonization of an organic complex and conductive carbon cross-linked, and the organic complex is formed by complexing and gelling of multivalent metal ions and protonated amino organic matter, and a stable structure is formed by chemical reaction between the complex and the conductive carbon.
[0016] A lithium-ion battery comprises the above-mentioned silicon-oxygen-carbon negative electrode material.
[0017] The beneficial effects produced by the present invention are: (1) The present invention proposes a method for preparing a silicon-oxygen-carbon negative electrode material, which utilizes the adsorption of protonated amino groups and silicon-oxygen, and the coordinated chemical reaction on this basis to construct a uniform conductive coating layer. Specifically, the protonated amino organic matter has an attractive effect on the Si-O-terminal bond of silicon-oxygen, and further the amino groups on the surface of silicon-oxygen form bonds with graphitized carbon such as carbon tubes under the electrostatic action of metal ions to form a three-dimensional cross-linked stable carbon layer of graphitized carbon tubes and amorphous coating carbon. This coated carbon has three advantages: 1) The abundant nitrogen atoms in the carbon layer can effectively play a doping role, forming electronic defects to improve the conductivity of the carbon layer; 2) The protonated amino groups and silicon-oxygen attract each other to form a uniform coating; 3) The carboxyl graphitized carbon bonds on the basis of the amino-anchored silicon-oxygen surface, enhancing the compactness and stability of the carbon layer structure, effectively exerting its conductivity and structural stability, and promoting the reversible charge and discharge capacity. The material coating uniformity and conductivity are innovatively improved from the material structure.
[0018] (2) The silicon-oxygen-carbon negative electrode material prepared by the present invention is applied to lithium-ion batteries, which can significantly improve the specific capacitance and cycle stability of the battery. Specifically, the specific capacitance of the silicon-oxygen-carbon negative electrode material prepared in Example 1 of the present invention can reach 1741 mAh / g (current density is 100 mA / g), and at a current density of 1 A / g, the battery capacity retention rate reaches 80% after 300 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 These are SEM images of materials prepared in the examples and comparative examples of the present invention, wherein (a / d / g) are for Example 1; (b / e / h) are for Comparative Example 1; and (c / f / i) are for Comparative Example 2.
[0021] Figure 2 This is a surface TEM image of the material prepared in Example 1 of the present invention.
[0022] Figure 3 The first cycle charge and discharge curves of the materials of Example 1 and Comparative Examples 1 and 2 of the present invention.
[0023] Figure 4 The cycle performance of the sample prepared in Example 1 at a current density of 1 A / g for 300 cycles. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1 The preparation method of the silicon oxygen carbon negative electrode material of this embodiment comprises the following steps: (1) 0.003 g of carboxylated single-walled carbon nanotubes were dispersed in 50 mL of deionized water to obtain a dispersion; the dispersion was transferred to a ball mill, ball milled at 200 rpm for 1 h, and then 0.42 g of carboxymethyl cellulose was added and ultrasonically dispersed for 10 min to obtain a suspension; (2) adding 3 g of silicon dioxide powder to the suspension obtained in step (1), ultrasonically stirring at 500 rpm for 3 h to form a suspension; (3) Take 0.3g chitosan and dissolve it in 20mL deionized water. Slowly add 0.45g glacial acetic acid to the solution to form a protonated solution A. Add 0.2g zinc nitrate to solution A to form solution B. While rapidly stirring solution B at a speed of 800rpm, slowly add the suspension obtained in step (2). Stir at a speed of 500rpm for 3h in a water bath at 50°C and then spray dry. The obtained precursor is transferred to a sintering furnace. The temperature is raised to 700°C at 5°C / min under nitrogen atmosphere protection and sintered for 1h to obtain a silicon-oxygen-carbon negative electrode material, also known as carbon-coated silicon-oxygen powder.
[0026] The obtained silicon oxygen carbon negative electrode material was prepared into a slurry, coated and assembled into a lithium ion half-cell, and tested at a current density of 100mA / g. The first charge specific capacity reached 1741mAh / g, and the first efficiency was 78%.
[0027] Example 2 The preparation method of the silicon oxygen carbon negative electrode material of this embodiment comprises the following steps: (1) Dispersing 0.0015 g of carboxylated graphene into 50 mL of deionized water to obtain a dispersion; transferring the dispersion to a ball mill, ball milling at 400 rpm for 1 h, adding 0.5 g of polyvinyl pyrrolidone and performing ultrasonic dispersion for 2 h to obtain a suspension; (2) adding 3 g of silicon dioxide powder to the suspension obtained in step (1), ultrasonically stirring at 600 rpm for 2 h to form a suspension; (3) Take 0.3g of polyethyleneimine and dissolve it in 20mL of deionized water. Slowly add 0.45g of glacial acetic acid to the solution to form a protonated solution A. Add 0.3g of palladium nitrate to solution A to form solution B. While rapidly stirring solution B at a speed of 900rpm, slowly add the suspension obtained in step (2). Stir at a speed of 600rpm for 3h in an oil bath at 85°C and then spray dry. The obtained precursor is transferred to a sintering furnace. The temperature is raised to 750°C at 5°C / min under nitrogen atmosphere protection and sintered for 4h to finally obtain a silicon-oxygen-carbon negative electrode material, also known as carbon-coated silicon-oxygen powder.
[0028] The obtained silicon oxygen carbon negative electrode material was prepared into a slurry, coated and assembled into a lithium ion half-cell, and tested at a current density of 100mA / g. The first charge specific capacity reached 1780mAh / g, and the first efficiency was 81%.
[0029] Example 3 The preparation method of the silicon oxygen carbon negative electrode material of this embodiment comprises the following steps: (1) 0.0015 g of carboxylated graphene was dispersed in 50 mL of deionized water to obtain a dispersion; the dispersion was transferred to a ball mill, ball milled at 500 rpm for 1 h, and then 0.42 g of N,N-dimethylformamide was added and ultrasonically dispersed for 2 h to obtain a suspension; (2) adding 3 g of silicon dioxide powder to the suspension obtained in step (1), ultrasonically stirring at 600 rpm for 2 h to form a suspension; (3) Take 0.3g dopamine and dissolve it in 20mL deionized water. Slowly add 0.45g glacial acetic acid to the solution to form a protonated solution A. Add 0.2g palladium nitrate to solution A to form solution B. While rapidly stirring solution B at a speed of 1300rpm, slowly add the suspension obtained in step (2). Stir at a speed of 800rpm for 10min in an oil bath at 90°C and then spray dry. The obtained precursor is transferred to a sintering furnace. The temperature is raised to 800°C at 5°C / min under nitrogen atmosphere protection and sintered for 1h. Finally, a silicon-oxygen-carbon negative electrode material, also known as carbon-coated silicon-oxygen powder, is obtained.
[0030] The obtained silicon oxygen carbon negative electrode material was prepared into a slurry, coated and assembled into a lithium ion half-cell, and tested at a current density of 100mA / g. The first charge specific capacity reached 1680mAh / g, and the first efficiency was 80%.
[0031] Example 4 The preparation method of the silicon oxygen carbon negative electrode material of this embodiment comprises the following steps: (1) Dispersing 0.0015 g of carboxylated single-walled carbon nanotubes into 50 mL of deionized water to obtain a dispersion; transferring the dispersion to a ball mill, ball milling at 400 rpm for 1 h, adding 0.42 g of carboxymethyl cellulose, and performing ultrasonic dispersion for 1 h to obtain a suspension; (2) adding 3 g of silicon dioxide powder to the suspension obtained in step (1), ultrasonically stirring at 400 rpm for 3 h to form a suspension; (3) Take 0.3g of carboxymethyl chitosan and dissolve it in 20mL of deionized water. Slowly add 0.45g of glacial acetic acid to the solution to form a protonated solution A. Add 0.2g of cobalt nitrate to solution A to form solution B. While rapidly stirring solution B at a speed of 1000rpm, slowly add the suspension obtained in step (2). Stir at a speed of 600rpm for 3h in a water bath at 60°C and then spray dry. The obtained precursor is transferred to a sintering furnace. The temperature is raised to 700°C at 5°C / min under nitrogen atmosphere protection and sintered for 5h to finally obtain a silicon-oxygen-carbon negative electrode material, also known as carbon-coated silicon-oxygen powder.
[0032] The obtained silicon oxygen carbon negative electrode material was prepared into a slurry, coated and assembled into a lithium ion half-cell, and tested at a current density of 100mA / g. The first charge specific capacity reached 1752mAh / g, and the first efficiency was 79%.
[0033] Example 5 The preparation method of the silicon oxygen carbon negative electrode material of this embodiment comprises the following steps: (1) 0.002 g of carboxylated graphene was dispersed in 50 mL of deionized water to obtain a dispersion; the dispersion was transferred to a ball mill, ball milled at 500 rpm for 1 h, and then 0.42 g of polyvinyl pyrrolidone was added and ultrasonically dispersed for 1 h to obtain a suspension; (2) adding 3 g of silicon dioxide powder to the suspension obtained in step (1), ultrasonically stirring at 600 rpm for 2 h to form a suspension; (3) Take 0.3g of carboxymethyl chitosan and dissolve it in 20mL of deionized water. Slowly add 0.45g of glacial acetic acid to the solution to form a protonated solution A. Add 0.1g of copper nitrate to solution A to form solution B. While rapidly stirring solution B at a speed of 900rpm, slowly add the suspension obtained in step (2). Stir at a speed of 600rpm for 3h in a water bath at 60°C and then spray dry. The obtained precursor is transferred to a sintering furnace. The temperature is raised to 800°C at 5°C / min under nitrogen atmosphere protection and sintered for 5h. Finally, a silicon-oxygen-carbon negative electrode material, also known as carbon-coated silicon-oxygen powder, is obtained.
[0034] The obtained silicon oxygen carbon negative electrode material was prepared into a slurry, coated and assembled into a lithium ion half-cell, and tested at a current density of 100mA / g. The first charge specific capacity reached 1810mAh / g, and the first efficiency was 77%.
[0035] Example 6 The preparation method of the silicon oxygen carbon negative electrode material of this embodiment comprises the following steps: (1) 0.003 g of carboxylated single-walled carbon nanotubes were dispersed in 50 mL of deionized water to obtain a dispersion; the dispersion was transferred to a ball mill, ball milled at 200 rpm for 1 h, and then 0.2 g of carboxymethyl cellulose was added and ultrasonically dispersed for 10 min to obtain a suspension; (2) adding 3 g of silicon dioxide powder to the suspension obtained in step (1), ultrasonically stirring at 500 rpm for 3 h to form a suspension; (3) Take 0.9g chitosan and dissolve it in 20mL deionized water. Slowly add 0.45g glacial acetic acid to the solution to form a protonated solution A. Add 0.2g zinc nitrate to solution A to form solution B. While rapidly stirring solution B at a speed of 800rpm, slowly add the suspension obtained in step (2). Stir at a speed of 500rpm for 3h in a water bath at 50°C and then spray dry. The obtained precursor is transferred to a sintering furnace. The temperature is raised to 700°C at 5°C / min under nitrogen atmosphere protection and sintered for 1h to obtain a silicon-oxygen-carbon negative electrode material, also known as carbon-coated silicon-oxygen powder.
[0036] The obtained silicon oxygen carbon negative electrode material was prepared into a slurry, coated and assembled into a lithium ion half-cell, and tested at a current density of 100mA / g. The first charge specific capacity reached 1750mAh / g, and the first efficiency was 78%.
[0037] Example 7 The preparation method of the silicon oxygen carbon negative electrode material of this embodiment comprises the following steps: (1) Dispersing 0.003 g of carboxylated single-walled carbon nanotubes into 50 mL of deionized water to obtain a dispersion; transferring the dispersion to a ball mill, ball milling at 200 rpm for 1 h, adding 0.5 g of carboxymethyl cellulose, and performing ultrasonic dispersion for 10 min to obtain a suspension; (2) adding 3 g of silicon dioxide powder to the suspension obtained in step (1), ultrasonically stirring at 500 rpm for 3 h to form a suspension; (3) Take 0.3g chitosan and dissolve it in 20mL deionized water. Slowly add 0.45g glacial acetic acid to the solution to form a protonated solution A. Add 0.2g zinc nitrate to solution A to form solution B. While rapidly stirring solution B at a speed of 800rpm, slowly add the suspension obtained in step (2). Stir at a speed of 500rpm for 3h in a water bath at 70°C and then spray dry. The obtained precursor is transferred to a sintering furnace. The temperature is raised to 700°C at 5°C / min under nitrogen atmosphere protection and sintered for 1h. Finally, a silicon-oxygen-carbon negative electrode material, also known as carbon-coated silicon-oxygen powder, is obtained.
[0038] The obtained silicon oxygen carbon negative electrode material was prepared into a slurry, coated and assembled into a lithium ion half-cell, and tested at a current density of 100mA / g. The first charge specific capacity reached 1861mAh / g, and the first efficiency was 77.4%.
[0039] Comparative Example 1 The method for preparing the silicon oxygen carbon negative electrode material of this comparative example is different from Example 1 in that glacial acetic acid is not added in step (3), and the steps are as follows: (1) 0.003 g of carboxylated single-walled carbon nanotubes were dispersed in 50 mL of deionized water to obtain a dispersion; the dispersion was transferred to a ball mill, ball milled at 200 rpm for 1 h, and then 0.42 g of carboxymethyl cellulose was added and ultrasonically dispersed for 10 min to obtain a suspension; (2) adding 3 g of silicon dioxide powder to the suspension obtained in step (1), ultrasonically stirring at 500 rpm for 3 h to form a suspension; (3) Take 0.3 g of chitosan and dissolve it in 20 mL of deionized water to form solution A. Add 0.2 g of zinc nitrate to solution A to form solution B. While rapidly stirring solution B at a speed of 800 rpm, slowly add the suspension obtained in step (2). Stir at a speed of 500 rpm for 3 h in a water bath at 50 ° C and then spray dry. The obtained precursor is transferred to a sintering furnace, and the temperature is raised to 700 ° C at 5 ° C / min under nitrogen atmosphere protection. Sinter for 1 h to finally obtain a silicon-oxygen-carbon negative electrode material, also known as carbon-coated silicon-oxygen powder.
[0040] The obtained silicon oxygen carbon negative electrode material was prepared into a slurry, coated and assembled into a lithium ion half-cell, and tested at a current density of 100mA / g. The first charge specific capacity reached 676.2mAh / g, and the first efficiency was 55%.
[0041] Comparative Example 2 The preparation method of the silicon oxygen carbon negative electrode material in this comparative example is different from Example 1 in that no metal salt is added in step (3), and the steps are as follows: (1) 0.003 g of carboxylated single-walled carbon nanotubes were dispersed in 50 mL of deionized water to obtain a dispersion; the dispersion was transferred to a ball mill, ball milled at 200 rpm for 1 h, and then 0.42 g of carboxymethyl cellulose was added and ultrasonically dispersed for 10 min to obtain a suspension; (2) adding 3 g of silicon dioxide powder to the suspension obtained in step (1), ultrasonically stirring at 500 rpm for 3 h to form a suspension; (3) Take 0.3g chitosan and dissolve it in 20mL deionized water, slowly add 0.45g glacial acetic acid to the solution to form a protonated solution A. While rapidly stirring solution A at a speed of 800rpm, slowly add the suspension obtained in step (2), stir at a speed of 500rpm for 3h in a water bath at 50°C, then spray dry, transfer the obtained precursor to a sintering furnace, heat it to 700°C at 5°C / min under nitrogen atmosphere protection, sinter for 1h, and finally obtain a silicon-oxygen-carbon negative electrode material, also known as carbon-coated silicon-oxygen powder.
[0042] The obtained silicon oxygen carbon negative electrode material was prepared into a slurry, coated and assembled into a lithium ion half-cell, and tested at a current density of 100mA / g. The first charge specific capacity reached 1373mAh / g, and the first efficiency was 61.8%.
[0043] Implementation effect example (1) Surface morphology test The microstructure of the prepared samples was measured using a Hitachi S~3400N scanning electron microscope. Figure 1 shown. Figure 1 Figures (a / d / g), (b / e / h) and (c / f / i) correspond to the SEM images of samples prepared in Example 1, Comparative Example 1 and Comparative Example 2, respectively. The comparison shows that the sample morphology of Example 1 is spherical, which is different from the sample morphology of Comparative Example 1 and Comparative Example 2. Compared with Example 1, Comparative Example 1 lacks the protonation process, resulting in no force between the amino organic matter and the silicon oxide particles, resulting in no force between the coating and the coated object, and the comparative example does not form a compact spherical structure. In addition, Comparative Example 2 lacks multivalent metal ions compared with Example 1. The protonated amino organic compound fails to produce a complexation in the absence of metal ion complexing sites, and the force between the particles is weak. The SEM image shows that there is agglomeration and the spherical structure is not good. Figure (f) also verifies that the thickness of its carbon layer is thinner than Figure (d) of the embodiment. Figure 2 This is a partial picture of the surface carbon coating layer of Example 1. It can be clearly seen that the amorphous carbon layer is fused with a graphitized lattice carbon structure, indicating that the surface coating structure presents a three-dimensional carbon layer in which the amorphous coating carbon and the crystalline graphitized carbon cross-penetrate each other.
[0044] (2) Battery assembly and electrochemical performance testing The silicon-oxygen negative electrode material prepared by the present invention is slurried with a conductive agent and a binder in a mass ratio of 8:1:1, uniformly coated on a copper foil and dried to obtain a pole piece, wherein the binder is polyacrylic acid (PAA). 6 The electrolyte solution, wherein the volume ratio of the solvent components ethylene carbonate (EC): diethyl carbonate (DEC): dimethyl carbonate (DMC) is 1:1:1, and 10% fluoroethylene carbonate (FEC) is added. A microporous polypropylene diaphragm is selected, and a lithium sheet is used as a counter electrode to assemble a CR2025 button half-cell. Comparative Example 1-2 The battery is assembled according to the above method, and the battery performance is tested using a battery test system model LANHE CT2001A produced by Wuhan Landian Electronics Co., Ltd.
[0045] The first cycle test uses a current density of 100mA / g and a voltage range of 0.005~2.0V. The constant current cycle performance test is carried out at 25℃, with a current density of 100mA / g and a voltage range of 0.005~2V. Figure 3The first cycle charge and discharge specific capacity and first coulombic efficiency of the material prepared by the method of Example 1 are better than those of Comparative Examples 1 and 2. This is because a uniform coating layer is formed on the surface of the silicon oxide particles, which improves the conductivity of the material, accelerates carrier transport, and releases the activity of the negative electrode material. Figure 4 The sample prepared in Example 1 has a cycle performance of 300 cycles of charge and discharge at a current density of 1 A / g. It can be seen that the battery capacity retention rate reaches 80% after 300 cycles.
[0046] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a silicon-oxygen-carbon negative electrode material, characterized in that: Here are the steps: (1) Dispersing conductive carbon in deionized water to obtain a dispersion; grinding the dispersion, adding a stabilizer to disperse the dispersion, and then adding silicon oxide powder to obtain a suspension; (2) dispersing an amino organic compound in deionized water, adding glacial acetic acid to form a protonated solution A; adding a metal salt to solution A to form a solution B; adding the suspension to solution B under stirring conditions, subjecting the solution to a chemical reaction, and spray drying to obtain a precursor; (3) In an inert atmosphere, the precursor is carbonized at high temperature to obtain the silicon-oxygen-carbon negative electrode material.
2. The method for preparing the silicon oxygen carbon negative electrode material according to claim 1, characterized in that: In the step (1), the conductive carbon is one or more of carboxylated single-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes and carboxylated graphene; and the stabilizer is one or more of carboxymethyl cellulose, polyvinyl pyrrolidone and N,N-dimethylformamide.
3. The method for preparing the silicon oxygen carbon negative electrode material according to claim 2, characterized in that: In the step (1), the amount of the stabilizer added is 0.4-1wt% of the mass of the dispersion; the mass ratio of silicon dioxide powder to conductive carbon is 1000-2000:
1.
4. The method for preparing the silicon oxygen carbon negative electrode material according to claim 3, characterized in that: In the step (2), the amino organic compound is at least one of chitosan, polyethyleneimine derivatives, chitosan derivatives, polyethyleneimine and dopamine; the metal salt is Pd 2+ 、Co 2+ 、Ni 2+ 、Zn 2+ Cu 2+ nitrate or acetate.
5. The method for preparing the silicon oxygen carbon negative electrode material according to claim 4, characterized in that: The mass of the amino organic compound in step (2) is 10-30% of the mass of silicon oxide.
6. The method for preparing the silicon oxygen carbon negative electrode material according to claim 5, characterized in that: In the step (2), the mass ratio of the amino organic compound, glacial acetic acid and metal salt in solution B is 1:1.5:(0.3-1).
7. The method for preparing the silicon oxygen carbon negative electrode material according to claim 6, characterized in that: The temperature of the chemical reaction in step (2) is 50-90°C.
8. The method for preparing the silicon oxygen carbon negative electrode material according to claim 7, characterized in that: In the step (3), the high temperature carbonization temperature is 700-800°C and the time is 1-5h.
9. A silicon-oxygen-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The silicon oxygen carbon negative electrode material is composed of a three-dimensional cross-linked stable carbon layer coated on the surface of silicon monoxide, wherein the three-dimensional cross-linked carbon layer is formed by high-temperature carbonization of an organic complex and conductive carbon, the complex is formed by complexing and gelling of organic matter with multivalent metal ions and protonated amino groups, and a stable structure is formed by chemical reaction between the complex and the conductive carbon.
10. A lithium ion battery, characterized in that: Including the silicon oxygen carbon negative electrode material as described in claim 9.
Citation Information
Patent Citations
Porous silicon-carbon composite cathode material as well as preparation method thereof and lithium ion battery
CN107994225A
High-rate silicon-oxygen-carbon material as well as preparation method and application thereof
CN114284481A
Cited By
High-capacity nitrogen-doped porous silicon-oxygen-carbon negative electrode material as well as preparation method and application thereof
CN120809769A